Reconfigurable beam steering parasitic patch antenna with embedded pin diode - Muzammil Jusoh (School of Computer and Communication Engineering, 2013)
The work described in this dissertation focuses on the reconfigurable beam steering antenna functionality for point-to-multipoint wireless communication application. This concept helps to reduce the antenna size, cost, and gives more flexibility for a customer premises equipment (CPE) to be operated in several modes.